Subclinical abnormal glucose tolerance is a predictor of death in liver cirrhosis - García Compeán, Diego; Jáquez Quintana, Joel Omar; Lavalle González, Fernando Javier; González González, José Alberto; Muñoz Espinosa, Linda Elsa; Villarreal Pérez, Jesús Zacarías; Maldonado Garza, Héctor Jesús (WJG Press, 2014)
AIM: To determine if subclinical abnormal glucose tolerance (SAGT) has influence on survival of non-diabetic patients with liver cirrhosis. METHODS: In total, 100 patients with compensated liver cirrhosis and normal fasting plasma glucose were included. Fasting plasma insulin (FPI) levels were measured, and oral glucose tolerance test (OGTT) was performed. According to OGTT results two groups of patients were formed: those with normal glucose tolerance (NGT) and those with SAGT. Patients were followed every three months. The mean follow-up was 932 d (range of 180-1925). Survival was analyzed by the Kaplan-Meyer method, and predictive factors of death were analyzed using the Cox proportional hazard regression model. RESULTS: Of the included patients, 30 showed NGT and 70 SAGT. Groups were significantly different only in age, INR, FPI and HOMA2-IR. Patients with SAGT showed lower 5-year cumulated survival than NGT patients (31.7% vs 71.6%, P = 0.02). Differences in survival were significant only after 3 years of follow-up. SAGT, Child-Pugh B, and high Child-Pugh and Model for EndStage Liver Disease (MELD) scores were independent predictors of death. The causes of death in 90.3% of cases were due to complications related to liver disease. CONCLUSION: SAGT was associated with lower survival. SAGT, Child-Pugh B, and high Child-Pugh and MELD scores were independent negative predictors of survival.